PROFILE AND TREATMENT SEEKING PATTERN OF MARRIED WOMEN WITH INFERTILITY RESIDING IN RURAL AREA OF NORTHERN KARNATAKA-A CROSS SECTIONAL STUDY. - Christina Karthaka MD; Padmaja R Walvekar PhD (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objectives: According to WHO globally over 60 to 80 million couples suffer from infertility among which 10% are women who are inflicted. Infertility is a serious public health issue with social consequences but is often neglected as it does not cause physical disability. Reproductive and Child Health (RCH) has a limited focus on services for infertile couples. Current study explores the profile of married women with infertility and their treatment-seeking patterns. Material&Methods: A community-based sectional Study was conducted between 1st January to December 31st, 2019 among 485 married women of reproductive age (15 to 49 years) with infertility residing in the field practice area of KLE JNMC by doing house-to-house visits with ASHA worker. Ethical clearance was obtained from the Institutional Review Board (IRB). Results: The majority of infertile women were between 26 to 35 years age group. Around 48% completed secondary schooling, and 80% were housewives belonging to the nuclear family and class II socioeconomic class (SES). Around 70% did not have any knowledge about fertile days in a menstrual cycle and there was a significant association between family history and primary infertility. Around 70% sought allopathic treatment and 32.7% did not seek treatment due to economic reasons. Conclusions: RMNCH+A includes reproductive and sexual health components, however infertility component is neglected. Hence this study explores the profile of infertile women and the need to include the infertility component in the RCH Programme.